2014
DOI: 10.1159/000365784
|View full text |Cite
|
Sign up to set email alerts
|

Compound <b><i>Astragalus</i></b> and <b><i>Salvia miltiorrhiza</i></b> Extract Suppresses Rabbits' Hypertrophic Scar by Modulating the TGF-β/Smad Signal

Abstract: Background: Hypertrophic scar is a fibro-proliferative disease. Our previous studies demonstrate that compound Astragalus and Salvia miltiorrhiza extract (CASE) inhibits proliferation and invasion in keloid fibroblasts. Objective: To investigate the effects of CASE on hypertrophic scar. Methods: Rabbits were divided into the control, model and three dosage groups of CASE (0.94, 1.88, 3.76%). An animal model of hypertrophic scar was established and treated with CASE ointment or ointment base. The histopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…TGF-β1 binds with TGF-β receptor II and then activates TGF-β receptor I on the cell membrane. Activated TGF-β receptor I phosphorylate receptor-regulated Smads (Smad2 and Smad3), and then the engagement of phosphorylated Smad2/3 with Smad4 allows for translocation into the nucleus and regulation of target gene transcription [29,35]. In this study, we examined the phosphorylation levels of Smad2 and Smad3 to explore the potential underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 binds with TGF-β receptor II and then activates TGF-β receptor I on the cell membrane. Activated TGF-β receptor I phosphorylate receptor-regulated Smads (Smad2 and Smad3), and then the engagement of phosphorylated Smad2/3 with Smad4 allows for translocation into the nucleus and regulation of target gene transcription [29,35]. In this study, we examined the phosphorylation levels of Smad2 and Smad3 to explore the potential underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Smad4 belongs to the family of Smad proteins and is a common mediator in the signal transduction processes of the TGF-β family ( 25 ). TGF-β expression can lead to fibroblast proliferation and ECM deposition ( 26 , 27 ). The present findings indicated that the mRNA and protein expression levels of Smad4 were downregulated in the scar-free repair group.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings implicating TGF-β1, smad2 and smad3 in HS formation have been reported by Chen et al ( 45 ). Therefore, blockage of the fibrotic processes mediated by TGF-β1/smad signaling is a potential therapeutic target for prevention and treatment of HS ( 46 48 ). In this study, we treated HS in rabbit ear model with different EFD of ESWT and found no significant difference in the expression of TGF-β1, smad2 and smad7.…”
Section: Discussionmentioning
confidence: 99%